Response of municipal solid waste to mechanical compression - Zekkos, Dimitrios; Fei, Xunchang; Grizi, Athina; Athanasopoulos, George (American Society of Civil Engineers, 2017)
The compressibility of municipal solid waste (MSW) is of engineering interest as it affects the short-term and long-term performance of landfills, as well as their expansion, closure, and postclosure development. An assessment of the field settlement behavior of MSW can be reliably executed only when the various mechanisms contributing to the settlement are properly taken into account. A comprehensive large-size experimental testing program that involved a total of 143 one-dimensional compression tests from five landfills, in Arizona, California, Michigan, and Texas of the United States as well as Greece was executed to systematically assess the compressibility characteristics of MSW subjected to a compressive load. Emphasis is given to the influence of waste structure, waste composition, unit weight, and confining stress on the compressibility parameters that are used in engineering practice, such as the constrained modulus and compression ratio, as well as long-term compression ratio due to mechanical creep only. The effect of waste composition and unit weight on the compressibility parameters is quantified. It is also found that the type of waste constituent (i.e., paper, plastic, or wood), as well as the waste’s anisotropic structure can have an effect on the compressibility characteristics of soil-waste mixtures. The proposed relationships can be used to estimate compressibility parameters of MSW at any degradation state as long as the waste composition and unit weight are known.